Investigating The Values of Guidance and Counseling in Eleganaboi - Da Costa, Augusto; Goncalves, Agostinho Dos Santos; Pereira, Sebastiao; Moreira, Paulo De Jesus (Jurnal Kajian Bimbingan dan Konseling, 2019)
Eleganaboi was a traditional ceremony in Luro society which contained essential elements of local wisdom. This study aimed to investigating the values of guidance and counseling in Eleganaboi. To investigate the values of guidance and counseling, we use phenomenology qualitative descriptive method. To collect the data, we implemented observation and interview. The observations were carried out during a cultural ceremony in the Luro community. Furthermore, interview was conducted on four traditional leaders. Edicts and transcendental reduction were used to analyze data. The results show eleven fundamental values of guidance and counseling in Eleganaboi. Those values are: gratitude; genuine; humble; honest; discipline; coherent; respect; care; trust; inclusive and togetherness. The community utilized Eleganaboi as a method to guide and counsel each member, including who faced problems in their life.